Technological and Pedagogical Knowledge in Relation to Teaching Proficiency among Criminology Faculty - Amba, Rey James; Jala, Chibert (Journal of Interdisciplinary Perspectives, 2024)
The transition from traditional face-to-face to online learning as an alternative course during the pandemic shifts different factors toward educators. This study determined the technological and pedagogical knowledge about teaching proficiency among criminology faculty. Quantitative research using a descriptive-correlational design involved 103 respondents from the selected schools offering criminology programs in the province of Misamis Oriental who were selected through purposive sampling. The instruments used in this study were the Technological Survey Questionnaire, the Pedagogical Survey Questionnaire, and the Teaching Proficiency Evaluation adopted from Witting. The findings showed that most of the respondents were young adults, mostly females with master's degree units, served less than five years and had contractual employment. The level of technological knowledge among criminology faculty was average. Somehow, the level of teaching proficiency among criminology faculty was high. The teachers' technical knowledge of word processing was significant to pedagogy, multimedia to course packages, and basic internet to course packages. Integration, communication technology, and assessment were significantly related to mastery of content and pedagogy. Teachers' motivation was significant to the integration and communication technology; instruction was highly significant to mastery of content, pedagogy, and integration and communication technology. The assessment was significant for mastery of content, pedagogy, and ICT integration. It is recommended that further studies be conducted using strong qualitative tools to investigate deep technological and pedagogical knowledge about teaching competence.